Metode Analisis Paracetamol (Acetaminophen) dalam Darah, Plasma, Dan Serum Manusia - Diah Muldianah; Sulastri Sulastri; Adelia Fatharani; Diany A. Nurdimayanthi; Dinda S. Rahmawati; Hana Fadhilah (Publikasi Indonesia, 2022)
Paracetamol (Acetaminophen) is one of the drugs most often prescribed to patients, ranging from children to the elderly, as a pain reliever by inhibiting prostaglandin synthesis in the central nervous system. Paracetamol has a broad therapeutic index with an adult dose of 500-1000 mg each time, with an interval of 4-6 hours. The review article aims to compare the analysis and sample preparation methods used to detect paracetamol in human blood, plasma, and serum. In compiling this article, the search method for research journals via the internet was used with Google. The results obtained showed that the detection of paracetamol in blood and serum was analyzed using the Gas Chromatography-Mass Spectrometry (GC-MS) with SPE (Solid Phase Extraction) sample preparation method while in plasma it was analyzed using several methods, namely Liquid Chromatography-Mass Spectrometry (LC-MS), High-Performance Liquid Chromatography-Mass Spectrometry (HPLC-MS), and Ultra-High-Performance Liquid Chromatography-Mass Spectrometry (UHPLC-MS) with protein precipitation and liquid-liquid extraction sample preparation methods. Among the four methods, the HPLC-MS method is considered fast, selective, and sensitive to analyzing paracetamol